Enrollment and financial projection for Fellowship Baptist College High School Department Kabankalan, Negros Occidental, school year 1985-1986 to 1987-1988 - Frias, Concepcion J. (Animo Repository, 1985)
This study seeks to determine the enrolment trend and financial status of Fellowship Baptist College High School Department for the past years covering school years 1980-81 to 1984-85 and 1981-82 to 1984-85, respectively. It also seeks to determine the projected enrolment trend and financial status of the school for the school year 1985-86 to 1987-88. The study used the descriptive method of research to determine and interpret the trends of enrolment for the past five years and income for the past four years. The records of past enrolment (enrolment records from school year 1980-1981 to school year 1984-85) and financial statements (from school year 1981-1982 to school year 1984-85) as sources of data were reviewed and studied to get the trends or retention rates and rates of increase for the past five years. The average growth rate provided the data on the rate of increase or decrease of the freshmen enrolment for the past five years. The average retention rate of students, common-size percentages, trend ratios and operation per student ratio were also determined.Findings of the study showed that the school was operating beyond its allocated budget. It also showed that there was no definite pattern in the enrollment trend.